Relationship between Helicobacter pylori status and serum pepsinogens as serologic markers in atrophic gastritis - (:unkn) unknown (My University, 2006)
Background/aims: Serum pepsinogen levels are considered as a non-endoscopic blood test in the diagnosis of atrophic gastritis. The objective of the present study was to investigate whether there is any difference between pepsinogen levels in Helicobacter pylori-positive and -negative patients with atrophic gastritis, and to analyze the relationship between histopathology and pepsinogen levels after treatment in H. pylori-positive patients with atrophic gastritis. Methods: The study enrolled a total of 30 cases with atrophic gastritis (18 H. pylori-positive and 12 H. pylori-negative). The H. pylori-positive cases received a one-week eradication treatment. Initially for all and after the treatment for H. pylori-positive cases, serum pepsinogen I and II levels, anti-H. pylori IgG titration and histopathologic analysis were carried out. Results: In the H. pylori-positive patients with atrophic gastritis, the levels of pepsinogen I and pepsinogen I/II ratio were lower while the levels of pepsinogen II were higher compared to the H. pylori-negative patients (p<0.05 for all). The post-treatment serum pepsinogen I levels and pepsinogen I/II ratios did not change in the H. pylori-positive group, while the levels of pepsinogen II, H. pylori antibody titration and gastric atrophy degree remarkably decreased (p<0.05 for all). Conclusions: In atrophic gastritis, the levels of serum pepsinogen and pepsinogen I/II ratio show a difference in H. pylori-negative versus -positive cases. Additionally, the usage of pepsinogen II as a serum marker in predicting the eradication of H. pylori with atrophic gastritis could be more reliable than pepsinogen I or the I/II ratio.
Keywords: Atrophic gastritis; Eradication; Helicobacter pylori; Pepsinogen; Serology